Adeka Palmarole becomes Adeka Polymer Additives Europe. Issue 1 (January 2018) - Unknown
Abstract : French polymer additives company Adeka Palmarole SAS has been renamed Adeka Polymer Additives Europe SAS, effective from 1 January 2018.